Digital transformation and sustainable development in Vietnam: Current situation, solutions and expected efficiency - Nguyen Thi Bich Loan; Vu Thi Thuy Hang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
The fourth industrial revolution has changed the global economy and many countries. Many achievements of this revolution have been used by countries, in which transformation has become an indispensable part, of development. Digital transformation helps countries have many opportunities for sustainable economic development, creating new jobs, reducing costs, and improving competitiveness. In recent times, Vietnam's digital economy has developed quite rapidly, the telecommunications information technology infrastructure is quite good, with wide coverage, and high user density, and Vietnam's population is young, relatively well-trained, and hard-working. Hard-working, passionate about technology, quick to adapt to change. Those are advantages for Vietnam to strongly digitally transform under the direction of the Government. The Government has created a new vitality for businesses and people to share and develop. This article approaches the content of digital transformation not from a technological perspective but based on the Government's perspective and orientation on digital transformation associated with sustainable development of Vietnam's economy until 2030, with a vision to 2030. 2045. From the current situation of digital transformation and sustainable development in our country, the article proposes several recommendations related to the development of digital government, digital economy, and digital society to achieve the expected effectiveness of digital transformation. Digital change associated with sustainable development in the context of globalization. Code: 23120402